The role of the sports manager in improving human relations in sports administration - Boudiaf, nawal (sports creativity, 2025)
Sports management is a key tool for achieving the goals of organizations related to physical education and sports through the optimal use of available capabilities, resources, and facilities. Believing in the importance of leadership that is advanced in its styles and practices, and in order for this tool to perform its role with high efficiency and effectiveness, the success of sports management depends on the extent to which its director and employees understand each other and the extent to which friendly relationships are established among them within an organizational climate that is dominated by democracy. When the director's dealings with employees are ideal, this will undoubtedly reflect on the sports management process. As a result, it is necessary to consider the psychological aspects of others, because humans are created weak, love to hear kind words, and are also inclined towards good treatment. Therefore, raising the morale of employees in general increases the individual's efficiency and effectiveness, because the higher the morale, the more it leads to increased and improved performance and thus the achievement of the desired goals. This requires a director who possesses a set of characteristics and qualities, such as human skills, that enable him to perform his leadership role through the art of dealing with employees in sports management.